2020
DOI: 10.1177/0363546520972418
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Matrix Components in the Developing Human Meniscus

Abstract: Background: Treatment of meniscal tears is necessary to maintain the long-term health of the knee joint. Morphological elements, particularly vascularity, that play an important role in meniscal healing are known to change during skeletal development. Purpose: To quantitatively evaluate meniscal vascularity, cellularity, collagen, and proteoglycan content by age and location during skeletal development. Study Design: Descriptive laboratory study. Methods: Medial and lateral menisci from 14 male and 7 female ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…The posterior regions of both minipig menisci were significantly wider than their respective anterior and central regions, similar to human menisci; the posterior region of the lateral minipig meniscus, the widest by average in this study, was only 2% smaller than the average width reported for the lateral meniscus in the human. Additionally, comparable to what is seen in humans ( Chevrier et al, 2009 ; Fedje-Johnston et al, 2021 ), histology of minipig meniscus cross sections showed a collagen network throughout the tissue, a positive staining for GAG, and cells dispersed throughout the tissue ( Figure 3 ). Overall, minipig knee menisci provide gross morphological similarities to humans in terms of their peripheral height and regional width, which could allow for the ready implantation and, eventually, translation of engineered tissues for their repair or replacement.…”
Section: Discussionsupporting
confidence: 75%
“…The posterior regions of both minipig menisci were significantly wider than their respective anterior and central regions, similar to human menisci; the posterior region of the lateral minipig meniscus, the widest by average in this study, was only 2% smaller than the average width reported for the lateral meniscus in the human. Additionally, comparable to what is seen in humans ( Chevrier et al, 2009 ; Fedje-Johnston et al, 2021 ), histology of minipig meniscus cross sections showed a collagen network throughout the tissue, a positive staining for GAG, and cells dispersed throughout the tissue ( Figure 3 ). Overall, minipig knee menisci provide gross morphological similarities to humans in terms of their peripheral height and regional width, which could allow for the ready implantation and, eventually, translation of engineered tissues for their repair or replacement.…”
Section: Discussionsupporting
confidence: 75%
“…Because of the rarity of the specimens, we decided to pool the data. Fedje-Johnston et al 13 recently reported a higher cell density for the medial compared with the lateral meniscus in a cohort aged 1 month to 11 years. Crawford et al 7 could not detect a difference in vessel penetration between the medial and lateral meniscus.…”
Section: Discussionmentioning
confidence: 92%
“…The American Journal of Sports Medicine 2021;49 (13):3544-3550 DOI: 10.1177/03635465211039865 Ó 2021 The Author(s) outcome measures at a minimum 2-year follow-up, regardless of the meniscal tear zone. The authors recommend repair for meniscal tears in all 3 vascular zones, although improved outcomes can be achieved when the repairs are performed in the RR and RW zones.…”
Section: Demonstrated Significant Improvements In Subjectivementioning
confidence: 99%
“…The search identified 411 articles, of which 352 were excluded based on title and abstract screening, and another twentyfive after full-text reading (Figure 2) [24]. Thirteen studies were included, which reported on patient characteristics affecting the microvasculature of the human meniscus (Table 1) [11][12][13][27][28][29][30][31][32][33][34][35][36], and another eleven studies reported on therapies enhancing the microvascularization of meniscal tissue (Table 2) [37][38][39][40][41][42][43][44][45][46][47]. Quality of the included studies, as assessed by the AQUA tool, is provided in Table 3.…”
Section: Literature Searchmentioning
confidence: 99%
“…Ten studies (3 HQ, 3 IQ, and 4 LQ) reported the effect of age on the microvascularization of the human meniscus (Table 1) [11][12][13][27][28][29][30][31][32]35]. Cadaveric studies have shown that the entire meniscus is vascularized around birth, but with increasing age, the vascularity gradually decreases from the inner to the peripheral margin [11,28].…”
Section: Agementioning
confidence: 99%